Thinness in Capital Markets: The Case of the Tel Aviv Stock Exchange - Silber, William L. (Journal of Financial and Quantitative Analysis, 1975)
A market is commonly called thin if a large change in price is associated with a small change in supply or demand. The concept of thinness can refer to the markets for stocks, bonds, any category of financial instrument, or even any type of good. Most frequently, thinness has been casually discussed with regard to bond markets and stock markets.